НАВЧАННЯ МАЙБУТНІХ ВЧИТЕЛІВ АНГЛІЙСЬКОЇ МОВИ З ВИКОРИСТАННЯМ КОМП’ЮТЕРНИХ ВПРАВ - Chufarchileva, A (Continuing Professional Education: Theory and Practice, 2019)
The article deals with teaching to future teachers of the English language writing summaries with the help of the computer exercises. The peculiarities of the process of the work with text are distinguished and such stages as planning, preliminary stage, realization and control are defi ned. Each of the above-mentioned stages of writing summary is characterized. The existing methodical requirements to exercises and the advantages of studying with the help of computer technologies are analyzed. The realization of the requirements to each component of a computer exercise is illustrated. The main forms of teaching students creating summaries with the help of information technologies are determined.